Awake Surgical Management of Third Ventricular Tumors: A Preliminary Safety, Feasibility, and Clinical Applications Study. Issue 2 (12th February 2019) - Chakravarthi, Srikant S; Kassam, Amin B; Fukui, Melanie B; Monroy-Sosa, Alejandro; Rothong, Nichelle; Cunningham, Joseph; Jennings, Jonathan E; Guenther, Neil; Connelly, Jeremy; Kaemmerer, Tobias; Nash, Kenneth C; Lindsay, Mark; et al.
Abstract: BACKGROUND: Endoscopic and microneurosurgical approaches to third ventricular lesions are commonly performed under general anesthesia. OBJECTIVE: To report our initial experience with awake transsulcal parafascicular corridor surgery (TPCS) of the third ventricle and its safety, feasibility, and limitations. METHODS: A total of 12 cases are reviewed: 6 colloid cysts, 2 central neurocytomas, 1 papillary craniopharyngioma, 1 basal ganglia glioblastoma, 1 thalamic glioblastoma, and 1 ependymal cyst. Lesions were approached using TPCS through the superior frontal sulcus. Pre-, intra-, and postoperative neurocognitive (NC) testing were performed on all patients. RESULTS: No cases required conversion to general anesthesia. Awake anesthesia changed intraoperative management in 4/12 cases with intraoperative cognitive changes that required port re-positioning; 3/4 recovered. Average length of stay (LOS) was 6.1 d ± 6.6. Excluding 3 outliers who had preoperative NC impairment, the average LOS was 2.5 d ± 1.2. Average operative time was 3.00 h ± 0.44. Average awake anesthesia time was 5.05 h ± 0.54. There were no mortalities. CONCLUSION: This report demonstrated the feasibility and safety of awake third ventricular surgery, and was not limited by pathology, size, or vascularity. The most significant factor impacting LOS was preoperative NC deficit. The most significant risk factor predicting a permanent NC deficit was preoperative 2/3 domain impairment combined with radiologic evidence of invasion of limbic structures – defined as a "NC resilience/reserve" in our surgical algorithm. Larger efficacy studies will be required to demonstrate the validity of the algorithm and impact on long-term cognitive outcomes, as well as generalizability of awake TPCS for third ventricular surgery.